Smoking prevalence, exposure to secondhand smoke, and factors associated with smoking among medical, dental, and pharmacy students in a public university in Malaysia - Rashidi Mohamed; Isa Naina-Mohamed; Jaya Kumar; Nadzmi Teh (Tobacco Induced Diseases)
Introduction Smoking among medical, dental, and pharmacy students is an issue in every university worldwide, which will impact future smoking cessation services as they are future healthcare providers. This study investigates the smoking prevalence, exposure to secondhand smoke, and factors associated with smoking among medical, dental, and pharmacy students at a public university in Malaysia.